2019
DOI: 10.1111/ics.12524
|View full text |Cite
|
Sign up to set email alerts
|

Localization, fate and interactions of Emilin‐1 in human skin

Abstract: Abstracts Objective Emilin‐1 is a versatile protein abundant in tissues where resilience and elastic recoil are prominent and interacting with components of the extracellular matrix. Still, little is known about Emilin‐1 in the skin. Therefore, we investigated Emilin‐1 in the skin, its localization, its fate upon ageing, its interactions with other proteins and the effect of its knockdown. Methods Skin explants from young or old Caucasian women, immunofluorescently labelled by anti‐Emilin‐1, anti‐Fibrillin‐1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…We observed that cells overexpressing EMILIN-1 had no directed migration, suggesting that its overexpression impair effective migration in melanoma cells. Previous analysis of Emillin1 expression in the skin showed that it locates in the dermis, up to the basement membrane, interacting with components of the ECM but also with the anchoring complex suggesting an important role for cell adhesion, migration, proliferation [45]. Directional cell motility is critical during inflammation, embryogenesis, and cancer metastasis [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that cells overexpressing EMILIN-1 had no directed migration, suggesting that its overexpression impair effective migration in melanoma cells. Previous analysis of Emillin1 expression in the skin showed that it locates in the dermis, up to the basement membrane, interacting with components of the ECM but also with the anchoring complex suggesting an important role for cell adhesion, migration, proliferation [45]. Directional cell motility is critical during inflammation, embryogenesis, and cancer metastasis [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that some overexpressed genes belonged to proteins hyper-secreted in sEVs from B16-F1R2. Interestingly, out of several candidates we selected EMILIN-1, a protein related to ECM and lymph node remodeling [ 23 ], that was hyper-secreted in sEVs and also overexpressed at the mRNA level ( Figure 1 F, Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Elastin microfibrillar interface proteins (EMILINs) constitute a four-member family of glycoproteins with a C-terminus gC1q domain typical of the gC1q/TNF superfamily members and also contain N-terminus unique cysteine-rich EMI domain [ 20 ]. EMILIN-1 has been characterized in multiple scenarios such as cell migration [ 21 ] and proliferation [ 20 ], cell migration [ 21 ], lymphatic vessel function [ 22 ] skin homeostasis [ 23 ], and cancer development [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…EMILIN1 interacts with components of the ECM, namely fibrillin and elastin, that together assemble into a complex network of elastic fibers which plays a pivotal role in the mechanical properties of the lamina propria and the quality of phonation [ 38 , 39 ]. It also binds to components of the basement membrane, including collagen I and LN322, which are part of the anchoring complex [ 40 ]. EMILIN1 interacts with the TGFβ1 precursor complex and maintains TGFβ1 in a latent state [ 41 ] and, thereby, could suppress its mitogenic effects.…”
Section: Discussionmentioning
confidence: 99%